Mathematical problem-solving abilities of deaf student in solving non-routine problems - Samuel Igo Leton; Meryani Lakapu; Wilfridus Beda Nuba Dosinaeng (STKIP PGRI Banjarmasin, 2019)
The purpose of this study was to obtain an overview of mathematical problem-solving abilities of class VIII deaf students in solving non-routine problems related to fractional problems. The type of research used is qualitative research with a case study design. Subjects were taken purposively at three Special Schools (SLB) B spread across Indonesia. Data was collected through problem-solving tests and interviews. The results of the analysis of the results of the work data and interview data, obtained that mathematical abilities that appear on the subject in solving problems include; (1) there is a tendency that in building understanding of the problem, the subject represents the problem through the picture, can reveal what is known and what is asked, identify the elements that are known, and restate the problem in a simpler language; (2) The subject can do elaboration namely linking information with knowledge that has been formed; (3) If deaf students can solve the problem, then to solve the problem tends to use images and use the method of counting. Thus, it can be concluded that deaf students can solve non-routine questions with a high degree of difficulty by first visualizing the problem in the form of images and writing back in simple sentences.